Analisis Faktor-Faktor Kepuasan Auditee atas Kinerja Inspektorat sebagai Auditor (Studi Empiris pada Pemerintah Daerah Kota Madiun Tahun 2012) - Handayani, Dwi (Widya Warta, 2013)
Auditing aims to ensure the implementation of     public accountability by both the central government and local government. The purpose of this study was to analyze the determinants of auditees’ satisfaction in the local government of Madiun. The object of this study was the agency/SKPD of Madiun government involved in the implementation of the financial administration of the area (the area of financial management powers) and responsible for the budget. It is an empirical study making use of purposive sampling technique to collect the data. The data were obtained through questionnaires. The questionnaires were 76 in number including 2 office heads, 1office secretary,11section heads, 16 sub- section heads, and 13 teasurers. The data were analyzed with the use of SPSS 15.0. The result of the study indicated that there were four variables which had relation with the auditees’ satisfaction namely, experience, industry expertise, member characteristics, and skeptical attitude. In addition, there were seven variables which had no relation with the auditees’ satisfaction. They are responsiveness, compliance, profesional care, commitment, executive involvement and conduct of audit field work.